Is long-term serum preservation suitable for research studies? Effect of time and temperature on the measurement of anti-Leishmania antibodies in canine sera samples - Diana Marteles; María Eugenia Lebrero; Sergio Villanueva-Saz; Clara Esteban Sanz; Víctor Martín; Antonio Fernández; Pablo Quilez; Maite Verde; Patricia Galan-Malo; M. Dolores Pérez (Veterinary Quarterly)
The stability of immunoglobulin G (IgG) antibodies is critical for diagnostic and research applications in veterinary medicine. This study evaluated the long-term stability of anti-Leishmania infantum IgG in canine serum samples under different storage conditions (−20 °C and −80 °C) over 2.5 years. Fifty-six serum samples were classified based on antibody concentration into low, medium, and high positive groups using an in-house enzyme-linked immunosorbent assay. Each sample was divided into aliquots and analyzed after different storage times (6 months, 1 year, 1.5, and 2.5 years). No statistically significant differences were observed in IgG concentrations across storage durations or between storage temperatures. Median antibody levels remained consistent, with minor variations attributed to assay-related variability. Correlation analyses showed strong agreement between initial and final measurements (R2 = 0.859 at −20 °C, R2 = 0.957 at −80 °C). The study underscores the suitability of −20 °C and −80 °C storage for preserving anti-Leishmania antibodies, providing valuable insights for serological diagnostics and research in veterinary science. Proper sample handling and aliquoting are recommended to maintain antibody integrity in routine diagnostics and long-term studies.